Intersecting Realms: Analyzing Impediments to Efficient Transit Operations in Maritime Ports - Mehlabani, Ehsan Gorjian; Chandramohanan, Akash (Management Analytics and Social Insights, 2024)
Transit assumes a pivotal role for nations adept at navigating the intricate currents of the global geopolitical landscape, offering a unique intersection of economic, social, political, and security considerations that set it apart from other industries. The present research endeavors to meticulously identify and analyze the practical impediments constraining optimal transit operations in Noshahr. Adopting an exploratory and survey-based research approach, the study focuses on the personnel associated with the ports and shipping administrations of Mazandaran province, with specific attention to the staff of Noshahr port and other relevant ports during the 2012-2013 temporal domain. The sample, comprising 300 individuals, is judiciously selected employing the Cochran formula designed for an unknown population. Statistical hypothesis scrutiny involves the application of factor analysis tests for component delineation, incorporating the Jem technique and T-test for the acceptance or rejection of identified components. The research reveals that various political, economic, institutional, technological, and geographical factors exert substantial influence over Neoshahr port export operations. Moreover, the empirical findings underscore the pronounced impact of these identified barriers in significantly diminishing the efficiency and efficacy of transit operations within the Noshahr port environs. This study contributes to the academic discourse surrounding transit dynamics and provides practical insights that can inform strategic interventions to enhance the operational landscape of Noshahr Port and, by extension, bolster the broader transit framework.